2019
DOI: 10.4081/monaldi.2019.1007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of uric acid serum levels on carotid arterial stiffness and intima-media thickness: A high resolution Echo-Tracking Study

Abstract: Serum uric acid (UA) has been shown to be a predictor of cardiovascular (CV) morbidity and mortality, and it may play a role in the pathogenesis of CV disease affecting vascular structure and function. However, there is limited evidence of its specific association with carotid artery stiffness and structure. The aim of our study was to evaluate whether UA is associated with early signs of atherosclerosis, namely local carotid arterial stiffness and intima-media thickening. We evaluated 698 consecutive asymptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 47 publications
0
11
1
1
Order By: Relevance
“…Duplicate publications, lectures and review articles (n = 58), as well as articles that were not relevant to the subject and did not meet the inclusion criteria (n = 256), were excluded. The remaining 139 studies were screened after reading the full text, and 15 studies were included in the meta-analysis [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The specific process is shown in Fig 1.…”
Section: Literature Screening Processmentioning
confidence: 99%
“…Duplicate publications, lectures and review articles (n = 58), as well as articles that were not relevant to the subject and did not meet the inclusion criteria (n = 256), were excluded. The remaining 139 studies were screened after reading the full text, and 15 studies were included in the meta-analysis [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The specific process is shown in Fig 1.…”
Section: Literature Screening Processmentioning
confidence: 99%
“…Uric acid (UA) is the end product of purine metabolism in humans, and approximately 70% of UA load is eliminated through the kidneys [ 7 ]. In the general population, hyperuricemia has been associated with many CV anomalies, including increased local arterial stiffness, carotid intima-media thickness, LVH, and atherosclerosis [ 8 , 9 , 10 , 11 , 12 ]. In patients with CKD, hyperuricemia has also been associated with many adverse CV outcomes, and high rates of CV events and CV mortality [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present issue of the Monaldi Archives of Chest Disease, Francesco Antonini-Canterin et al [21] report a study investigating the carotid ultrasound assessment of UA effect on carotid beta stiffness index (BSI) and intima-media thickness (CIMT). In a large sample of patients with high CV risk but no history of coronary artery disease, heart failure or cardiomyopathies, with normal or elevated UA levels, the authors found a significant correlation between UA levels and BSI and CIMT.…”
Section: Monaldi Archives For Chest Disease 2019; Volume 89:1057mentioning
confidence: 99%